Microwave-assisted hydrothermal extraction of natural malic acid for the synthesis of low transition temperature mixtures - Yiin, C.L. (Elsevier Ltd, 2016)
This work describes the utilization of microwave hydrothermal extracted malic acid from cactus, lophatherum herb, papaya and Luffa cylindrica as hydrogen bond donor for the synthesis of natural low transition temperature mixtures (LTTMs) with sucrose as hydrogen bond acceptor. The effects of parameters including reaction temperature, extraction time, mass of sample and oxidant, H2O2 were discussed. The saturation equation was used to fit with the experimental data, observing only a slight loss of the goodness of fit. The optimum conditions for microwave hydrothermal extraction were found to be at 1 g of sample, 200 Â°C and 45 min in the presence of hydrogen peroxide (H2O2) as oxidant. Consequently, the proposed method was successfully applied to extract malic acid from plants and fruits for the synthesis of LTTMs. The LTTMs prepared from the extracted malic acid have identical physicochemical properties with the LTTMs derived from commercial malic acid due to the existence of hydrogen bond and the ability to dissolve lignin. Â© 2015 Elsevier Ltd.